MANAGEMENT PRACTICES IN ELDERLY CARE: DIFFERENCE BETWEEN MUSLIM AND JEWISH ELDERLY POPULATIONS IN ISRAELI NURSING HOMES - Yonatan Elgabsy (Економіка та суспільство)
In Israeli society, the perception of nursing homes differs between Arab and Jewish populations. For Arab Muslims, family plays a central role in elderly care, considering it a core value in Arab culture. This study examines the elderly's involvement in deciding to move to a nursing home and utilize formal community services. Findings show that family members in the Arab community struggle with this decision, and the high involvement of the elderly themselves provides legitimacy to the decision. Muslim families take longer to decide regarding transferring to a nursing home than Jewish families, indicating the decision's complexity. Factors contributing to this matter include limited knowledge about nursing homes, lack of adapted institutional services, and difficulty obtaining culturally aligned medical care. The study highlights the need for culturally sensitive institutional services and increased knowledge accessibility. These findings can guide policymakers and healthcare providers in developing tailored solutions to address the unique needs of Israel's elderly population across diverse cultural and religious backgrounds.